KEPUTUSAN PENGAMBILAN KREDIT PEMILIKAN RUMAH (KPR) PENGARUH BRAND AWARENESS, PHYSICAL EVIDENCE DAN SERVICE QUALITY PADA PT. BTN (PERSERO) Tbk - Therecia, Hillary; Hermanto, Y. Budi; Widyastuti, maria (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2021)
This research aims to determine the effect of brand awareness, physical evidence and service quality on mortgage decisions at Bank BTN Branch Office Surabaya Bukit Darmo. The sampling method are purposive sampling method with sample size of 100 respondents. The results showed that: (1) there is a positive and significant impact of brand awareness on the decisions to make KPR at Bank BTN Surabaya Bukit Darmo Branch office (2) There is a positive and significant effect of physical evidence on decision to make KPR at Bank BTN Surabaya Bukit Darmo Branch Office (3) there is a positive and significant effect of service quality on the decisions to make KPR at Bank BTN Surabaya Bukit Darmo Branch Office; and the regression coefficient is 0.314. (4) The influence of brand awareness, physical evidence and service quality on mortgage decisions at Bank BTN Surabaya Bukit Darmo Branch Office (adjusted R2) is 79.7%.